Disentangling the neurological basis of chronic ocular pain using clinical, self-report, and brain imaging data: use of K-means clustering to explore patient phenotypes - Holmes, Scott; Reyes, Nicholas; Huang, Jaxon J.; Galor, Anat; Pattany, Pradip M.; Felix, Elizabeth R.; Moulton, Eric A. (Frontiers in Neurology, 2023)
The factors that mediate the expression of ocular pain and the mechanisms that promote chronic ocular pain symptoms are poorly understood. Central nervous system involvement has been postulated based on observations of pain out of proportion to nociceptive stimuli in some individuals. In this investigation, we recruited a total of 53 persons divided into two cohorts: persons who reported no ocular pain, and persons who reported chronic ocular pain, irrespective of ocular surface findings. We performed a resting state fMRI investigation that was focused on subcortical brain structures including the trigeminal nucleus and performed a brief battery of ophthalmological examinations. Persons in the pain cohort reported higher levels of pain symptoms relating to neuropathic pain and ocular surface disease, as well as more abnormal tear metrics (stability and tear production). Functional connectivity analysis between groups evinced multiple connections exemplifying both increases and decreases in connectivity including regions such as the trigeminal nucleus, amygdala, and sub-regions of the thalamus. Exploratory analysis of the pain cohort integrating clinical and brain function metrics highlighted subpopulations that showed unique phenotypes providing insight into pain mechanisms. Study findings support centralized involvement in those reporting ocular-based pain and allude to mechanisms through which pain treatment services may be directed in future research.